The role of supply chain event management systems for supply chain risk management - (:unkn) unknown (My University, 2009)
The Role of Supply Chain Event Management Systems for Supply Chain Risk Management Late delivery, breakdown of IT-systems or production machines, variations in demand, supply, tranportation are a few examples of risks that increase costs and reduce satisfaction of customers of an enterprise. If the relevant enterprise is an actor in a supply chain, then such risks do not only impact this enterprise but also those enterprises that are present in the upstream and downstream of the supply chain. Through the globalization of the economy such risk interdependencies along supply chains took on significance in the last years. In order to avoid these risks, risk management that concentrates on the entire supply chain is essential. This risk management is supported by various instruments among which Supply Chain Event Management Systems (SCEM-systems) also can be counted. This study aims to explain to what extent SCEM-systems support the risk management process in supply chains.
Keywords: Supply chain event management system; Supply chain risk management